Collaborative/competitive learning styles and students’ academic performance in cost accounting in federal universities in South-south, Nigeria - Chukwuka, Godspower Kingsley; Pius, Ekpo Godwin (Journal of Social, Humanity, and Education, 2024)
Purpose: This study investigates the correlation between learning styles and students' academic achievement in the field of cost accounting among federal universities located in the south-south region of Nigeria. Research methodology: This study analyzed 556 final-year business education students from four federal universities in south-south Nigeria (source). The sample consisted of 248 students, selected using cluster sampling (source). The primary data were obtained using a questionnaire (source). The statistical method used was the Pearson Product Moment Correlation (PPMC) to evaluate the hypotheses and address. Results: The findings revealed a significant positive association between the two variables. Additionally, the analysis underscores the significant positive relationship between the competitive learning approach and students' academic performance in cost accounting in federal universities in the south-south region of Nigeria. Limitations: The sample size was small, which may have affected the reliability of the findings. Contribution: The study would also be of benefit to professional bodies such as ICAN, ANAN, NIT, and others in that they would be aware that students have different styles of learning their course contents. Novelty: The study advised educators to strategically design learning activities that would promote both collaboration and competition, while also establishing high-performance expectations for students. Practical implications: Instructors are also expected to help students develop these three different styles of learning, since cost accounting, a course studied at the university, involves many calculations and concepts.